Prevalence and correlates of anxiety and depression among family carers of cancer patients in a cancer care and treatment facility in Uganda: a cross-sectional study - Katende, Godfrey; Nakimera, Lillian (African Journals Online (AJOL), 2017)
Background: The process of caregiving may cause emotional distress in form of anxiety and depression among family carers of cancer patients. Little is known about the prevalence of anxiety and depression among family carers of cancer patients in Uganda. Objectives: To determine the prevalence of anxiety and depression and related factors associated with abnormal levels of anxiety and depression among family carers of cancer patients in a cancer care and treatment facility in Uganda. Methods: After obtaining ethical approval, we recruited family carers of cancer patients to this cross-sectional study. Data was collected with the use of the Hospital Anxiety and Depression Scale(HADS) standardized tool. Results: A total of 119 family carers were recruited from the Uganda Cancer Institute. The prevalence of anxiety and depression among family carers was high (45% V. 26 %); Abnormal levels of anxiety (ALA)(OR 0.27, 95% CI, p= 0.01) and depression (ALD)(OR 0.37, 95% CI, p=0.05) were significantly associated with being a relative carer. Conclusion: Anxiety and depression is prevalent among family carers of cancer patients. Being a relative carer predisposes you to increased risk of developing anxiety and depression. Incorporating evidence based psychological therapies into usual care and targeting family carers is imperative.